The Influence of Leverage, Liquidity, Profitability and Company Size on Dividend Policy - Indriani, Novi; Sukesti, Fatmasari; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
The type of research used by researchers is quantitative methods. Quantitative methods are research methods based on the philosophy of positivism, used to research certain populations or samples, data collection using analytical research instruments, data analysis is quantitative/statistical. Based on the results of analysis carried out on 72 samples over a 6 year period using multiple linear regression analysis, it shows that in the observation period (2017-2022) of the 4 hypotheses tested, only 3 were accepted, while 1 hypothesis was rejected